Mediating Role of Employee Readiness to Change in the Relationship of Change Leadership with Employees' Affective Commitment to Change - Najmuddin Somadi; Alice Salendu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to see whether the quality of change leadership affects affective commitment to change through a mediator of employee readiness to change at private hospital X which is changing organizational structure and leadership. The population of this study was employees of private hospital X with a sample of 212 employees. The measuring instrument used in this study is the Change Leadership Scale (Liu, 2010) with an alpha coefficient of 0.98, the Readiness for Organizational Changer Questionnaire (Holt, et al., 2007) with an alpha coefficient of 0.92, and Commitment to change Inventory (Herscovitch & Meyer, 2002) with an alpha coefficient of 0.79. This study was analyzed using Pearson correlation analysis and Hayes mediation (2018). The results showed that employees' readiness to change significantly as a mediator in the relationship between change leadership and affective commitment to change (b= 0.118, SE=0.024, p< 0.001, 95% CI [0.07, 0.16]). This research was carried out only until the design of the intervention program, namely reorientation and socialization was presented to representatives of private hospital X, this was due to changes in the Board of Directors and several company policies making intervention programs difficult for researchers to implement at this time. Based on the assessment of the presentation of the intervention program design, it shows that the representatives of private hospital X are satisfied with the program design and can be implemented after the establishment of a new policy by the management team.